2014
DOI: 10.1016/j.virol.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Viral fitness does not correlate with three genotype displacement events involving infectious hematopoietic necrosis virus

Abstract: Viral genotype displacement events are characterized by the replacement of a previously dominant virus genotype by a novel genotype of the same virus species in a given geographic region. We examine here the fitness of three pairs of infectious hematopoietic necrosis virus (IHNV) genotypes involved in three major genotype displacement events in Washington state over the last 30 years to determine whether increased virus fitness correlates with displacement. Fitness was assessed using in vivo assays to measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…In untreated sea water, virus survived for around 8 days at 4°C (Kell et al . ). Similarly, when incubated in wastewater from a fish processing plant (FPW, a mixture of UV‐filtered 95% sea water and 5% fresh water) at this temperature, 99.9% of the virus was inactivated in 7 days (Afonso et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In untreated sea water, virus survived for around 8 days at 4°C (Kell et al . ). Similarly, when incubated in wastewater from a fish processing plant (FPW, a mixture of UV‐filtered 95% sea water and 5% fresh water) at this temperature, 99.9% of the virus was inactivated in 7 days (Afonso et al .…”
Section: Resultsmentioning
confidence: 97%
“…However, viable virus was still detected after 9 weeks when incubated with previously sterilised suspensions of Kaolin, Japanese acid clay and diatomaceous earth at 4°C (Yoshinaka et al 2000). In untreated sea water, virus survived for around 8 days at 4°C (Kell et al 2014). Similarly, when incubated in wastewater from a fish processing plant (FPW, a mixture of UV-filtered 95% sea water and 5% fresh water) at this temperature, 99.9% of the virus was inactivated in 7 days (Afonso et al 2012).…”
Section: Infectious Haematopoietic Necrosis Virusmentioning
confidence: 99%
“…Competition may also be mediated by the innate immune response, which can take 24–48 h to fully activate in fish (Purcell et al, 2012). The studies on superinfection indicated that the interferon response was likely not the primary factor responsible for competitive exclusion (Kell et al, 2013, 2014), but it may be that other constitutive immune mechanisms are at play (Purcell et al, 2010, 2011). Ultimately, the mechanisms shaping competition for IHNV require further study.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been hypothesised that a U genogroup strain (or strains) jumped from sockeye salmon to rainbow trout, evolving into the M genogroup and having greater virulence for the new host and losing virulence for the original one [ 11 , 97 ]. The fitness of three pairs of IHNV M genotypes in the Columbia River basin was assessed by in vivo replication kinetics, host interferon-induced Mx-1 expression during single infections and the ability to replicate in co-infection and superinfection studies in steelhead trout [ 98 ]. Increased fitness did not correlate with displacement of one genotype by another in the field, suggesting that other factors were important for such displacement events, such as increased ability to shed into the water, leading to increased chance of transmission or increased ability to persist in the host leading to increased duration and distance of transmission.…”
Section: Virulence Of Ihnv Strainmentioning
confidence: 99%